Durabilidade da interface de união entre adesivo e dentina: efeito da adição de nanopartículas de cobre. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Objectives: This study evaluated the effect of addition of copper nanoparticles (CuNp) at different concentrations into a simplified etch-and-rinse (ER) adhesive system (Ambar [FGM]) on the immediate (IM), 1-year (1y), 2-years (2y) and 4-years (4y) resindentin bond strength (µTBS), nanoleakage (NL), and presence of copper nanoparticles (PC) within the hybrid layer. Methods: Seven experimental adhesive systems were formulated according to the addition of CuNp concentration (0 [control], 0.0075, 0.015, 0.06, 0.1, 0.5 and 1%). The occlusal enamel of thirty-five molars were removed and adhesives were applied to dentin surface after 37% phosphoric acid etching, followed by composite resin restorations. The specimens were longitudinally sectioned to obtain resin-dentin beam-like (0.8 ± 0,1 mm2) and were stored in distilled water at 37°C. From each tooth from each group, four specimens were tested in tension at 0.5mm/min at each time (µTBS). As for NL and PC, 1 resin-dentin beamlike of each tooth was prepared and analyzed by SEM. The µTBS and NL data of each adhesive were subjected to two-way repeated measures ANOVA. Tukey’s post hoc test was used for pair-wise comparisons (α = 0.05). Results: Addition of 0.5% CuNp in the adhesive system significantly increased the µTBS at IM (p < 0.05). After 1y, 2y and 4y, copper-containing adhesives showed higher values of µTBS (p < 0.05), excepted for 0.075% CuNp after 2y. All adhesives showed a significant decrease in µTBS over time (p < 0.05), except for 1% CuNp (p ≥ 0.05). Significant decreases in the NL values were observed in the copper-containing adhesives at IM (p < 0.05). After 1y, 2y and 4y, adhesives with 0.075% to 1% of CuNp showed significant decrease in NL values. Copper-containing adhesives showed a significant increase in NL only after 4y (p < 0.05). Presence of copper within the hybrid layer was identified from 0.06% concentration at IM and after 4y. Conclusion: The addition of copper nanoparticles in concentrations from 0.06% to 0.5% is an alternative to improve the adhesive properties at immediate time and to decrease the degradation of the adhesive interface over time.
Keywords: Adesivos Convencionais; Dentina; Resistencia de união; Nanoinfiltração; Presença de cobre; Etch-and-rinse; Adhesives; Dentin; Copper; Microtensile bond strength; Nanoleakage; Presence of copper; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA